Endocrine disrupting activities and geochemistry of water resources associated with unconventional oil and gas activity - Kassotis, Christopher D. (Sci Total Environ, 2020)
The rise of hydraulic fracturing and unconventional oil and gas (UOG) exploration in the United States has increased public concerns for water contamination induced from hydraulic fracturing fluids and associated wastewater spills. Herein, we collected surface and groundwater samples across Garfield County, Colorado, a drilling-dense region, and measured endocrine bioactivities, geochemical tracers of UOG wastewater, UOG-related organic contaminants in surface water, and evaluated UOG drilling production (weighted well scores, nearby well count, reported spills) surrounding sites. Elevated antagonist activities for the estrogen, androgen, progesterone, and glucocorticoid receptors were detected in surface water and associated with nearby shale gas well counts and density. The elevated endocrine activities were observed in surface water associated with medium and high UOG production (weighted UOG well score-based groups). These bioactivities were generally not associated with reported spills nearby, and often did not exhibit geochemical profiles associated with UOG wastewater from this region. Our results suggest the potential for releases of low-saline hydraulic fracturing fluids or chemicals used in other aspects of UOG production, similar to the chemistry of the local water, and dissimilar from defined spills of post-injection wastewater. Notably, water collected from certain medium and high UOG production sites exhibited bioactivities well above the levels known to impact the health of aquatic organisms, suggesting that further research to assess potential endocrine activities of UOG operations is warranted.